Immunotherapy and Targeted Therapies in Treatment of Visceral Leishmaniasis: Current Status and Future Prospects - Singh, Om Prakash; Sundar, Shyam (Frontiers in Immunology, 2014)
Visceral leishmaniasis (VL) is a vector-borne chronic infectious disease caused by the protozoan parasite Leishmania donovani or Leishmania infantum. VL is a serious public health problem, causing high morbidity and mortality in the developing world with an estimated 0.2 -0.4 million new cases each year. In the absence of a vaccine, chemotherapy remains the favoured option for disease control, but is limited by a narrow therapeutic index, significant toxicities, and frequently acquired resistance. Improved understanding of VL pathogenesis offers the development of immune based treatment options either alone or in combination with chemotherapy. Modulations of host immune responses include the approaches that inhibit molecular pathways, crucial for parasite growth and maintenance; and stimulate host effectors immune responses that restore the impaired effector functions. In this review, we highlight the challenges in treatment of VL with a particular emphasis on immunotherapy and targeted therapies to improve clinical outcomes.